2007
DOI: 10.1037/0894-4105.21.3.346
|View full text |Cite
|
Sign up to set email alerts
|

Alcoholism and judgments of affective stimuli.

Abstract: This study sought to differentiate alcoholism-related changes in judgments of emotional stimuli from those of other populations in which such changes have been documented. Two sets of visual stimuli, one containing words and the other containing drawings of faces (representing a range of emotional content), were presented to abstinent alcoholic adults with and without Korsakoff's syndrome, as well as to a healthy control group and four groups of patients with other neurobehavioral disorders: Parkinson's diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 81 publications
5
45
1
1
Order By: Relevance
“…Moreover, AD participants were also more likely to interpret a happy face as expressing a negative mood. Similarly, Clark et al (2007) report that AD participants rated drawings and emotional words, across valences, as more intense than controls, and Kornreich et al (2013) report higher emotional intensity ratings to music, faces and voices by AD participants compared with controls. Taken together, these data suggest that a wide variety of emotional stimuli and emotional expressions are often interpreted differently by AD participants compared to controls.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Moreover, AD participants were also more likely to interpret a happy face as expressing a negative mood. Similarly, Clark et al (2007) report that AD participants rated drawings and emotional words, across valences, as more intense than controls, and Kornreich et al (2013) report higher emotional intensity ratings to music, faces and voices by AD participants compared with controls. Taken together, these data suggest that a wide variety of emotional stimuli and emotional expressions are often interpreted differently by AD participants compared to controls.…”
Section: Resultsmentioning
confidence: 90%
“…Alcohol abuse over a significant period, may well lead to slower cognitive skill, manifested in memory, mental speed and motor responses (Clark et al, 2007;OscarBerman and Marinkovic, 2003). There is also a high comorbidity between alcohol dependence and anxiety and depression with both these clinical conditions reported to heighten awareness of emotional stimuli (Williams et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, alcoholic individuals present a differential deficit for emotional stimuli, as they have preserved cognitive and semantic evaluation of emotional stimuli (e.g., Clark et al, 2007;Maurage et al, 2009), but impaired affective evaluation of these stimuli (e.g., Marinkovic et al, 2009;Uekermann et al, 2005). Alcoholism could thus be the first clinical condition to combine preserved cognitive and impaired emotional empathy.…”
mentioning
confidence: 99%
“…Studies also have shown evidence for impaired cognitive processing of simple emotions in alcohol-dependent patients (Clark et al, 2007;Kornreich et al, 2001aKornreich et al, , 2001bKornreich et al, , 2002Kornreich et al, , 2003Philippot et al, 1999;Townshend and Duka, 2003). Because poor neuropsychological function may be a risk factor for substance use disorders that are transmitted from parent to child, we hypothesized that poor perception of social information may likewise be a risk factor for substance use disorders and may be transmitted from parent to child, whether biologically or environmentally.…”
Section: S Tudies Have Consistently Reported Cognitive-function Defi mentioning
confidence: 99%